Employee Performance and Service Quality Strategy to Improve Customer Satisfaction at BPR Dhanatani Cepiring Brebes - Wahyuni Sri Rejeki; Adhitya Yoga Prasetya (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2024)
This study examines the relationship between service quality and employee performance in influencing customer satisfaction at BPR Dhanatani Cepiring Brebes, a rural bank operating in Central Java, Indonesia. Using a qualitative descriptive approach, the research explores how the bank’s service delivery processes, employee competencies, and organizational strategies collectively shape customer perceptions and loyalty. Data were collected through interviews, direct observations, and document analysis involving both employees and customers. The results reveal that employee performance and service quality exert a significant and interdependent influence on customer satisfaction. Superior service quality characterized by reliability, responsiveness, assurance, and empathy directly enhances satisfaction and customer trust. Meanwhile, high employee performance, supported by adequate training, motivation, and managerial supervision, improves operational consistency and service delivery. However, certain limitations remain, particularly in digital literacy, workload balance, and communication efficiency. The study concludes that sustainable customer satisfaction requires an integrated strategic framework that combines continuous human resource development, performance appraisal, and service process innovation. These findings contribute to the understanding of how rural banking institutions can strengthen customer relationships and competitiveness through a synergy between human capital and service quality management.